2016 IEEE Nordic Circuits and Systems Conference (NORCAS) 2016
DOI: 10.1109/norchip.2016.7792887
|View full text |Cite
|
Sign up to set email alerts
|

A CMOS MF energy harvesting and data demodulator receiver for wide area low duty cycle applications with 230 mV start-up voltage

Abstract: A low voltage start-up energy harvesting medium frequency receiver is presented, for use as the power and synchronisation part of a remote sensor node in a wide area industrial or agricultural application. The use of embedded low bandwidth network synchronisation data permits very low operational duty cycle without the need for real time clocks or wake up receivers at each node with their associated continuous power drain. The receiver consists of a rectifier, a power management unit and a phase-shift keying d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In uncontrolled environments, researchers have shown that low-frequency RF energy can be utilised over much larger distances compared to high-frequency counterparts such as GSM and WiFi [123]. A very exciting new development in wireless power transfer systems is the creation of a medium-frequency CMOS energy harvester [124]. This system offers the ability to embed a power source into any CMOS device, which can supply up to 10 μW and occupy just 0.54 mm 2 in silicon.…”
Section: Sources Of Energymentioning
confidence: 99%
“…In uncontrolled environments, researchers have shown that low-frequency RF energy can be utilised over much larger distances compared to high-frequency counterparts such as GSM and WiFi [123]. A very exciting new development in wireless power transfer systems is the creation of a medium-frequency CMOS energy harvester [124]. This system offers the ability to embed a power source into any CMOS device, which can supply up to 10 μW and occupy just 0.54 mm 2 in silicon.…”
Section: Sources Of Energymentioning
confidence: 99%